(untitled) (International Journal of Engineering and Computer Science, 2014)
In this paper we aim to propose a faster algorithm for solving the problem of ‘area of the union of iso-oriented rectangles’. For this purpose we use MapReduce which is a powerful tool in parallel data processing to divide the task among P separate processors. We utilize the Interval Tree data structure and Sweep Line technique to obtain a solution with time complexity